Grid Analysis of Timpah Isolated ULD System ni the de-Dieselization Program of PT PLN (Persero) UID Kalselteng – UP3 Kuala Kapuas - Eko Bagus Aribawa (Eduvest - Journal of Universal Studies, 2025)
The de-dieselisasi program has become a key strategy of PT PLN (Persero) in reducing dependence on diesel power plants in isolated areas, including ULD Timpah, Kapuas Regency, Central Kalimantan. This study aims to analyze the effectiveness of the grid system performance after the implementation of de-dieselisasi, focusing on technical, operational, and financial aspects. The method used is a descriptive quantitative approach with a case study, supported by primary and secondary data, as well as system simulations using the ETAP application. The results show that the electricity distribution voltage remained stable within operational standards, both before and after the project (20.54 kV to 19.17 kV). Operationally, the electricity service hours increased from 16 hours to 24 hours per day, improving the quality of service to customers. Initial financial analysis indicated that the project was not feasible; however, an avoided cost analysis resulted in a positive Net Present Value (NPV) of IDR 162.55 billion, demonstrating significant cost efficiency compared to diesel-based operations. In conclusion, the de-dieselisasi program at ULD Timpah successfully improved the efficiency, reliability, and sustainability of the electricity system in remote areas, providing positive impacts technically, operationally, and financially to support national electrification goals.